25(OH)D Levels in Infancy Is Associated With Celiac Disease Autoimmunity in At-Risk Children: A Case–Control Study - Andrén Aronsson, Carin; Liu, Xiang; Norris, Jill M.; Uusitalo, Ulla; Butterworth, Martha D.; Koletzko, Sibylle; Virtanen, Suvi M.; Erlund, Iris; Kurppa, Kalle; Hagopian, William A.; Rewers, Marian J.; She, Jin-Xiong; et al. (Frontiers in Nutrition, 2021)
Objectives An observed variation in risk of celiac disease according to season of birth suggests that vitamin D may affect the development of the disease. The aim of this study was to investigate if vitamin D concentration is associated with the risk of celiac disease autoimmunity in genetically at-risk children. Study design Children prospectively followed in the multinational The Environmental Determinants of Diabetes in the Young study, conducted at six centers in Europe and the USA were selected in a 1-to-3 nested case-control study. In total, 281 case-control sets were identified. celiac disease autoimmunity was defined as positivity for tissue transglutaminase autoantibodies (tTGA) on two or more consecutive visits. Vitamin D was measured as 25(OH)D concentrations in all plasma samples prior to, and including, the first tTGA positive visit. Conditional logistic regression was used to examine the association between 25(OH)D and risk of celiac disease autoimmunity. Results No significant association was seen between 25(OH)D concentrations (per nmol/L increase) and risk for celiac disease autoimmunity development during early infancy (odds ratio [OR] 0.99, 95% confidence interval [CI] 0.95- 1.04) or childhood (OR 1.02, 95% CI 0.97-1.07). When categorizing 25(OH)D concentrations there was an increased risk of celiac disease autoimmunity with 25(OH)D concentrations <30 nmol/L (OR 2.23, 95% CI 1.29, 3.84) and >75 nmol/L (OR 2.10, 95% CI 1.28-3.44) in early infancy, as compared to 50-75 nmol/L. Conclusion This study indicates that 25(OH)D concentrations <30 nmol/L and >75 nmol/L during early infancy were associated with increased risk of developing celiac disease autoimmunity in genetically at-risk children. The non-linear relationship raises the need for more studies on the possible role of 25(OH)D in the relation to celiac disease onset.